Environment-Related and Body-Related Components of the Minimal Self - Liesner, Marvin; Kunde, Wilfried (Frontiers in Psychology, 2021)
Perceptual changes that an agent produces by efferent activity can become part of the agent’s minimal self. Yet, in human agents, efferent activities produce perceptual changes in various sensory modalities and in various temporal and spatial proximities. Some of these changes occur at the ‘biological’ body, and are to some extent conveyed by ‘private’ sensory signals, whereas other changes occur in the environment of that biological body, and are conveyed by ‘public’ sensory signals. We discuss commonalties and differences of these signals for generating selfhood. We argue that despite considerable functional overlap of these sensory signals in generating self-experience, there is reason to tell them apart in theorizing and empirical research about development of the self.